Green Lantern : alliance - Lê, Minh, 1979- (DC Comics, 2022)
Tai Pham struggles with balancing school, his work in the family business, his friendships, and his new Green Lantern responsibilities, but Kid Flash arrives on the scene to become the super-hero partner Tai just might need.